PUBLIC DEFENDER'S OFFICE: HISTORICAL RETROSPECTIVES AND ADVANCES IN COLLECTIVE PROTECTION. (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2012)
The strengthening of fundamental rights gave rise to a new way of understanding access to justice, which was consolidated with the creation of the Public Defender's Office in the countries of Latin America, following a model designed by Spanish constitutionalism. In Brazil, its creation took place through the Federal Constitution of 1988, and since then it has undergone an increasing expansion in its spectrum of activity. The work of the Public Defender's Office in the collective field should be seen as an opportunity to guarantee spaces for the most disadvantaged, giving an active voice to the vulnerable, achieving the fullness of citizenship. The methodology used bibliographic research as a method of procedure and the method of approach is the bibliographic deductive. Finally, the approach perspective is qualitative, since it involves descriptive information.